Rhino Cerebral Mucormycosis - A Case Report - N Eswar; N Gnanasundaram (Wolters Kluwer Medknow Publications, 2006)
Rhino cerebral Mucormycosis is an opportunistic infection caused by a saprophytic fungus which is found in soil, decaying fruits and vegetables. Usually predisposing factors for this infection are poorly controlled diabetes, ketoacidosis, leukemia, immunodeficiency states, prolonged steroid therapy etc. The fungus once entering the susceptible host do cause highly invasive and fulminant infection usually with fatal outcome. Early recognition of this condition is highly essential to initiate immediate life saving measures.